Padrões estratigráficos holocênicos do Delta do Parnaíba através de testemunhos por vibração - Cruz, Diogo Bittencourt Leite Tinôco (2022)
The Parnaíba River Delta, located in northeastern Brazil, is one of the few examples of a deltaic depositional system that still has its characteristics well preserved, which makes it increasingly the target of scientific research in the most diverse areas. The present work aimed to identify changes in the depositional environment, based on the vertical analysis of sediments. Vibracores were collected in old mangrove forest, in active zones of tidal channels, and in supratidal swamp. The study included sediment analysis associated with petrophysics (Gamma Ray Spectrometry), as well as dating by the radiocarbon method using the Mass Spectrometry Accelerator technique. In a first phase, the gamma-ray spectral analysis and the photographic record of the cores were carried out, followed by the stratigraphic description (color, texture, presence of organic matter, fossil content, occurrence of sedimentary structures), as well as the identification and selection of material for dating (e.g. shells, wood). Subsequently, the cores were sampled at regular intervals, every 4 cm, for granulometric, compositional (organic matter, and calcium carbonate quantification) and mineralogical analyses. The results obtained showed mineralogical variations, indicating changes in sedimentary origin. The gamma-spectrometric data tend to show higher values with the decrease of the grain and associated to the sedimentological, stratigraphic and mineralogical data improves a better interpretation of the depositional history. The contents of organic matter and calcium carbonate, in general, presented variations related to the grain size, with fine sediments presenting higher contents of organic matter, while carbonate is related to the presence of shells. Datings showed ages ranging from 4.6 – 4.5 BP to more recent ages (1950 AD). The integration and joint analysis of the data allowed a better interpretation of the late Holocene evolution of the current system of tidal channels on the western and eastern margins of the Parnaíba river delta.